Race, policing, and public governance : on the other side of now - Williams, Brian N., 1967- (Cambridge : Cambridge University Press, 2021)
I can't breathe ... a haunting phrase moaned at the intersection of past and present, serving as an audible supplement to the visual evidence to yet another collision of race and policing. This phrase reflects the current state of police-community relations in the United States. But, what lies on the other side of now? This Element examines this salient question in the context of excessive use of force and through the lenses of race, policing and public governance. We draw upon extant research and scholarship on representative bureaucracy, public engagement in the co-creation of public polices and the co-production of public services, and the emerging findings from studies in network science, coupled with insights from elite interviews, to offer implications for future research, the profession of policing, the public policymaking process, public management, and post-secondary institutions.
Title from publisher's bibliographic system (viewed on 24 Jun 2021).
Keywords: Police administration; Race relations; Police-community relations